Healthcare professionals’ experiences of eHealth in palliative care for older people: challenges, compromises and the price of dignity - Rada Sandic Spaho; Lisbeth Uhrenfeldt; Theofanis Fotis; Jorunn Bjerkan; Ingjerd Gåre Kymre (International Journal of Qualitative Studies on Health & Well-Being)
Purpose To explore whether and how eHealth solutions support the dignity of healthcare professionals and patients in palliative care contexts. Method This qualitative study used phenomenographic analysis involving four focus group interviews, with healthcare professionals who provide palliative care to older people. Results Analysis revealed four categories of views on working with eHealth in hierarchical order: Safeguarding the patient by documenting—eHealth is a grain of support, Treated as less worthy by authorities—double standards, Distrust in the eHealth solution—when the “solution” presents a danger; and Patient first—personal contact with patients endows more dignity than eHealth. The ability to have up-to-date patient information was considered crucial when caring for vulnerable, dying patients. eHealth solutions were perceived as essential technological support, but also as unreliable, even dangerous, lacking patient information, with critical information potentially missing or overlooked. This caused distrust in eHealth, introduced unease at work, and challenged healthcare professionals’ identities, leading to embodied discomfort and feeling of a lack of dignity. Conclusion The healthcare professionals perceived work with eHealth solutions as challenging their sense of dignity, and therefore affecting their ability to provide dignified care for the patients. However, healthcare professionals managed to provide dignified palliative care by focusing on patient first.